Cover Feature: The Development of Biophotovoltaic Systems for Power Generation and Biological Analysis (ChemElectroChem 21/2019). Issue 21 (16th October 2019) - Wey, Laura T.; Bombelli, Paolo; Chen, Xiaolong; Lawrence, Joshua M.; Rabideau, Clayton M.; Rowden, Stephen J. L.; Zhang, Jenny Z.; Howe, Christopher J.
Abstract : The Cover Feature illustrates the production of extracellular electrons from photosynthetic microorganisms or subcellular fractions located on an electrode. Methods for studying extracellular electron production, developments in electrode design, the pathway for electron transfer to the electrode, and prospects for scale‐up are discussed in more detail in the article by L. Wey et al. More information can be found in the Minireview by L. T. Wey et al. on page 5375 in Issue 21, 2019 (DOI: 10.1002/celc.201900997 ).